Evaluation of the dependence of qualitative variables on the results of a pedagogical experiment - Zgurskaya, M. P; Nizhevskaya, T. V. (Problems of Engineer-Pedagogical Education, 2018)
The method of statistical verification of hypotheses about the independence of variables measured in the ordinal (dichotomous and ranked) scale of values is considered. The article presents the results of the analysis of dependencies between the qualification level of a higher technical education teacher and the degree of the acquisition of electrical engineering course material by students studying at higher educational institutions. The grouped results of the pedagogical experiment are presented in the work in the tables of conjugation of the ranks of the studied variables; such tables allow indirectly setting the accuracy of the test according to the level of significance. And, on the basis of this, a standard criterion of significance was used to assess the statistical effect of factors of interdependence of qualitative variables, which is very effective at a small number of levels. It is proved that criterion statistics χ2 can be used to assess the interdependence of variables in a pedagogical experiment.